COACHING DENGAN PENDEKATAN PEER EDUCATION TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU UPAYA PENCEGAHAN HIV/AIDS - ., Widjijati; ., Supadi; Wahyuningsih, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Problems unhealthy sexual behavior and drug use in adolescents resulting in adolescents vulnerable to contracting HIV / AIDS. In the world every year, the majority of humans infected with HIV in the 15-24 year age range. Every day nearly 6,000 teens in the world infected with HIV, this means that there are 250 teenagers are infected every hour of every day. Nearly 12 million young people living with the HIV-infected condition, adolescents under the age of 25 years the percentage is 28% of the total 42 million people living with HIV. This study aims to determine the effectiveness of coaching with the peer education approach to changes in knowledge, attitudes, and behavior of adolescents with HIV / AIDS. This type of research is the study quasi-experiment with pretest-posttest control group design. Sampling in this study was conducted using simple random sampling. Data were analyzed using paired t-test and independent t-test. Statistically by paired t test coaching peer education approach to significantly improve the knowledge (p = 0.000) and changing attitudes (p = 0.001) and behavior (p = 0.002) adolescents against HIV / AIDS. But the statistical test by independent t test coaching with peer education approach does not significantly increase the knowledge and changing attitudes and behavior of adolescents on HIV / AIDS (p = 0261). Â Keywords: teenagers, coaching, peer education, HIV / AIDS